Line Source of Water Application - An Appropriate Drip Irrigation System for Field Crops - Patel, Neelam; Rajput, TBS (Journal of Agricultural Engineering, 2003)
Drip irrigation system is generally adopted in widely spaced row crops by providing point source(s) of water application to individual plants. Its adoption for closely spaced field crops requires drip laterals to serve as line sources of water application. Widths of wetted strips under laterals having emission rates of 8, 10, 12 and 16 Lph/m were observed under durations of operation of 1, 2 and 3 hr, in a sandy loam soil. The wetted widths, in all the line sources were found increasing almost linearly with time as well as with increasing emission rates. A prediction equation (S = 6.914 + 6.70T + 2.786 q) was developed for determining the spacing between two adjacent laterals, S (cm) for a known operation duration, T (up to 3 hr) and emission rate of the laterals, q (ranging between 8 to 16 Lph/m).